The contribution of leg muscle power and eye-foot coordination to the accuracy of futsal shooting of students - Abiyyu Jikaladha Imka; Rices Jatra; Procopio B. Dafun JR (Khatulistwa Education Center, 2025)
Background Shooting accuracy is a fundamental skill in futsal, yet preliminary observations at State Junior High School 35 Pekanbaru showed that students still demonstrate low shooting performance, indicated by weak ball power, inaccurate ball direction, and poor foot–ball contact. These symptoms suggest inadequate leg muscle power and insufficient eye–foot coordination, which may inhibit students’ ability to perform accurate shots. Objectives This study aims to analyze the contribution of leg muscle power and eye–foot coordination to futsal shooting accuracy among students at State Junior High School 35 Pekanbaru. Methods This research employed a multiple-correlation design involving 15 students selected through total sampling. Leg muscle power was measured using the standing broad jump test, eye–foot coordination was assessed with a coordination test, and shooting accuracy was evaluated through a futsal shooting test. Data were analyzed using simple and multiple correlation techniques. Results The findings show that leg muscle power significantly contributes to shooting accuracy (r = 0.799; contribution = 63.84%). Eye–foot coordination also shows a significant contribution (r = 0.615; contribution = 37.82%). Simultaneously, both variables provide a substantial combined contribution to shooting accuracy (r = 0.800; contribution = 64%). Conclusion In conclusion, leg muscle power and eye–foot coordination are decisive determinants of students’ futsal shooting accuracy. The study contributes to educational practice by emphasizing the need for targeted physical and coordination training to support students’ motor skills development, thereby enhancing their confidence, engagement, and overall well-being through sports participation.